Applying ChatGPT as an AI Writing Assistant: EFL Teachers’ and Students’ Perceptions in a Senior High School in Sorong - Melva Yanti Sianturi; Andang Saehu; Sylvia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores the perceptions of EFL teachers and students regarding the use of ChatGPT as an AI writing assistant in English writing activities at a public senior high school in Sorong, Southwest Papua. The study is grounded in the Technology Acceptance Model (TAM), which examines perceived usefulness (PU), perceived ease of use (PEOU), attitude toward using (ATU), behavioral intention (BI), and actual use (AU). A qualitative case study approach was employed involving four English teachers and six eleventh-grade students who had experience using ChatGPT in writing activities. Data were collected through semi-structured interviews and documentation and analyzed using thematic analysis based on TAM constructs. The findings reveal that both teachers and students perceive ChatGPT as a useful tool for supporting English writing activities. Teachers reported that ChatGPT assists in generating teaching materials, writing prompts, and feedback more efficiently, while students found it beneficial for generating ideas, improving grammar, expanding vocabulary, and organizing their writing. Participants also perceived ChatGPT as easy to use due to its simple interface and accessible interaction process. Furthermore, both teachers and students demonstrated positive attitudes toward its use and expressed strong intentions to continue utilizing the tool in writing activities. These perceptions were reflected in their actual use of ChatGPT in routine teaching and learning practices. The study concludes that ChatGPT is perceived as a supportive tool in EFL writing instruction when used appropriately, highlighting the importance of pedagogical guidance to ensure responsible and effective integration of AI tools in language learning.